Pelatihan Penggunaan Lab Virtual Berbasis PhET Untuk Guru Sekolah Dasar dalam Pembelajaran IPA - Dedi Holden Simbolon; Eni Yusnita br Pardede; Theresia Perbina; Alena Rosiana Manik (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to enhance elementary school teachers’ competence in utilizing PhET Interactive Simulations as a virtual laboratory tool in science learning, particularly on the topic of “Changes in the States of Matter.” The program employed a workshop-based training model combined with two weeks of guided mentoring to ensure effective classroom implementation. The activities included technical training on operating PhET simulations, pedagogical training on designing inquiry-based lesson plans (RPP) and student worksheets (LKPD), independent practice sessions, and evaluation through pretest–posttest assessments and classroom observations. The results indicate a significant improvement in teachers’ technical and pedagogical skills, demonstrated by their ability to operate simulations independently, develop inquiry-oriented LKPD aligned with PhET features, and integrate simulations into structured inquiry learning steps. Classroom implementation further showed that PhET-based LKPD effectively increased students’ engagement, motivation, and conceptual understanding. In addition, post-training mentoring supported teachers in overcoming technical challenges and promoted sustainability of virtual laboratory practices at the school level. Overall, the program successfully strengthened teachers’ instructional capacity and supported more active, exploratory, and inquiry-based science learning aligned with the principles of the Merdeka Curriculum.